A novel economic analyzing method for CCHP systems based on energy cascade utilization. (15th September 2020) - Teng, Jiaying; Wang, Wan; Mu, Xiaofei
Abstract: A novel economic analyzing method was proposed to evaluate the combined cooling, heating and power (CCHP) system based on energy cascade utilization and the current feed-in tariff policy in China. Natural gas consumption rates were chosen as the economic criteria to evaluate operation costs of cooling, heating and electricity of an office building in Changchun, Jilin of China. Based on the building's energy consumption and current energy price structures, the following electric load (FEL) operation strategy was used to achieve a more profitable performance from the CCHP system. Because of the deficiency in economic performance, no excess electricity was generated or sold to the grid, even though selling electricity to the grid was allowed when certain restrictions were satisfied. Meanwhile, the power generation unit size was optimized according to the basic electric requirement of the building. Additionally, a water storage tank was used because it could improve the primary energy consumption ratio and the profitability of the CCHP system. Highlights: Natural gas consumption rate was used as an analysis index based on energy cascade utilization. Realistic feed-in tariff policies and energy price structures in China were taken into account. The optimized operation strategy and design of the CCHP system were proposed accordingly.